MORAL EDUCATION AS A REINFORCEMENT OF LEGAL EDUCATION IN AN EFFORT TO ACHIEVE PUBLIC COMPLIANCE WITH THE LAW - Yustia, rd. Dewi Asri (Faculty of Law, Universitas Pekalongan, 2024)
Legal education is one of the efforts made to provide legal awareness for the community, this needs to be done because it sees the phenomenon of increasingly rampant legal problems carried out by the community. If you look at the data on violations of the law released by the National Police, namely 276,507 crimes that occurred in Indonesia throughout 2022, and increased by 7.3% compared to the previous year, so it is estimated that crimes occur every 2 minutes when calculated every hour. Looking at the data, it can be seen that legal education that continues to be built and provided as if there is no benefit, no impact, so that it is as if legal education does not have any impact on changing people's behavior. How to strengthen legal education as an effort to provide legal awareness for the community, and how to model the right educational collaboration so that legal compliance by the community can be achieved. This study is the result of legal research using the legal approach and the norm approach as the basis of philosophy. Legal awareness is the awareness that exists in every human being about that law, a certain category of our lives by distinguishing between legal and non-law. Awareness of what law is means awareness that law is the protection of human interests, because law is a rule that has a function to protect human interests.